2007
DOI: 10.1111/j.1553-2712.2007.tb02026.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Crotalidae Polyvalent Immune Fab in Pediatric Crotaline Envenomations

Abstract: Background: Since it was approved by the Food and Drug Administration in October 2000, Crotalidae Polyvalent Immune Fab (CroFab) has largely replaced previously used crotaline antivenom. CroFab is more specifically tailored for crotalids of North America and is less allergenic than whole immunoglobulin antivenoms. However, premarketing and postmarketing studies have excluded children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 9 publications
(19 reference statements)
1
5
0
Order By: Relevance
“…They are currently used clinically for several indications, including digoxin toxicity (DigiFab) and snake envenomation (CroFab), and these products have excellent safety records (8,28,35). While human or humanized MAbs as immunotherapeutics have several advantages over animal-derived polyclonals as immunotherapeutic agents (long circulatory half-life, consistency of supply, and reduced humoral immune response), their high specificity and reliance on one, or a few, epitopes for efficacy may be a significant issue when targeting an antigen with known sequence diversity (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are currently used clinically for several indications, including digoxin toxicity (DigiFab) and snake envenomation (CroFab), and these products have excellent safety records (8,28,35). While human or humanized MAbs as immunotherapeutics have several advantages over animal-derived polyclonals as immunotherapeutic agents (long circulatory half-life, consistency of supply, and reduced humoral immune response), their high specificity and reliance on one, or a few, epitopes for efficacy may be a significant issue when targeting an antigen with known sequence diversity (18).…”
Section: Discussionmentioning
confidence: 99%
“…Ovine antibodies have been used widely clinically to treat intoxication (snake bite victims, drug overdose) and are well tolerated in humans (8,28,35). In general, polyclonal antibodies are particularly effective at neutralizing and clearing toxins from the bloodstream, and their diverse composition makes them efficient at neutralizing toxin families, such as C. difficile toxins A and B, where there is a significant level of sequence diversity.…”
mentioning
confidence: 99%
“…A literature review of controlled and observational studies confirmed the efficacy and safety of CroFab ® [67]. Crofab ® has also been demonstrated to be effective in paediatric patients [68,69]. However, a South American study demonstrated a locally produced whole IgG antivenin was more effective than two F(ab ) 2 preparations but with more anaphylactoid reactions [70].…”
Section: Efficacy and Safety Of Modern Polyclonal Immunoglobulin Prodmentioning
confidence: 93%
“…153 The antivenom is most effective when administered within 4 hours of the bite. The indications for the administration of CroFab TM to victims of snakebites are similar to the indications for antivenin (Crotalidae) polyvalent.…”
Section: Crotalidae Polyvalent Immune (Ovine) Fab (Crofab Tm )mentioning
confidence: 99%